Evaluasi Program Penyediaan Air Minum Dan Sanitasi Berbasis Masyakarat (PAMSIMAS) di Desa Purwosari II Kecamatan Tamban - Hayatun Nisa; Azwari, Trisylvana; Erma Ariyani; Avela Dewi; Rusiyana; Novi Shintia (Pencerah, 2023)
This research aims to evaluate PAMSIMAS program activities in Purwosari II Village. The method used is qualitative with descriptive research type. Data sources come from several sources, namely, primary data sources, namely the results of interviews with 10 informants and observations; second, secondary data taken from collecting documents, news, books, research reports, and articles. The results of PAMSIMAS research in Purwosari II Village seen from the criteria of equity, responsiveness and accuracy are quite good. Meanwhile, the criteria for effectiveness, efficiency and adequacy are still not good. The inhibiting factors in evaluating PAMSIMAS in Purwosari II Village are the socio-economic conditions of the community, lack of socialization about PAMSIMAS to the community, and PAMSIMAS raw materials using river water. The suggestions in this research are (1) For people who have economic problems, it is hoped that the village government can use village funds to help by eliminating payment of half the installation costs so that poor people can also enjoy the PAMSIMAS flow; (2) Socialization or dissemination of information about PAMSIMAS is being intensified again, both through electronic media and other means. Home visits must also be carried out evenly so that people who have not been touched or do not know and understand PAMSIMAS will know and understand better; (3) In the future, we hope that the village and PAMSIMAS managers will provide a water source for PAMSIMAS other than river water, for example from wells. The condition of the river water is uncertain and has acid levels and a taste that is too bland, making PAMSIMAS water unfit for drinking.